Improving clinical management of diabetic macular edema: insights from a global survey of patients, healthcare providers, and clinic staff - Ziemssen, Focke; Sylvanowicz, Michelle; Amoaku, Winfried M.; Aslam, Tariq; Eldem, Bora; Finger, Robert P.; Gale, Richard P.; Kodjikian, Laurent; Korobelnik, Jean-François; Lin, Xiaofeng; Loewenstein, Anat; Mitchell, Paul; et al. (Ophthalmology and therapy, 2025)
Introduction In contrast with patients receiving therapy for retinal disease during clinical trials, those treated in routine clinical practice experience various challenges (including administrative, clinic, social, and patient-related factors) that can often result in high patient and clinic burden, and contribute to suboptimal visual outcomes. The objective of this study was to understand the challenges associated with clinical management of diabetic macular edema from the perspectives of patients, healthcare providers, and clinic staff, and identify opportunities to improve eye care for people with diabetes. Methods We conducted a survey of patients with diabetic macular edema, providers, and clinic staff in 78 clinics across 24 countries on six continents, representing a diverse range of individuals, healthcare systems, settings, and reimbursement models. Surveys comprised a series of single- and multiple-response questions completed anonymously. Data gathered included patient personal characteristics, challenges with appointment attendance, treatment experiences, and opportunities to improve support. Provider and clinic staff surveys asked similar questions about their perspectives; and clinic characteristics were also captured. Results Overall, 5681 surveys were gathered: 3752 from patients with diabetic macular edema, 680 from providers, and 1249 from clinic staff. Too many appointments, too short treatment intervals, difficulties in traveling to the clinic or arranging adequate support to travel, out-of-pocket costs, office/parking fees, and long waiting times were noted by all as contributing to increase the burden on the patient and caregiver. Patients generally desired more in-depth discussions with their provider, which would help with information exchange and better expectation-setting. Conclusions The wealth of systematic data generated by this global survey highlights the breadth and scale of challenges associated with the clinical management of patients with diabetic macular edema. Addressing the opportunities for improvement raised by patients, providers, and clinic staff could increase patient adherence to treatment, reduce appointment burden, and improve clinic capacity.